2018
DOI: 10.1155/2018/3058640
|View full text |Cite
|
Sign up to set email alerts
|

Reviews of Interleukin-37: Functions, Receptors, and Roles in Diseases

Abstract: Interleukin-37 (IL-37) is an IL-1 family cytokine discovered in recent years and has 5 different isoforms. As an immunosuppressive factor, IL-37 can suppress excessive immune response. IL-37 plays a role in protecting the body against endotoxin shock, ischemia-reperfusion injury, autoimmune diseases, and cardiovascular diseases. In addition, IL-37 has a potential antitumor effect. IL-37 and its receptors may serve as novel targets for the study, diagnosis, and treatment of immune-related diseases and tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 88 publications
3
77
1
Order By: Relevance
“…39 Many studies have shown that IL-37 plays an important regulatory role in various inflammatory diseases (eg, asthma), autoimmune diseases (eg, rheumatoid arthritis), and tumors. 40 A number of studies show that it is downregulated in patients with severe keloids: the recent cross-sectional study by Khattab et al showed that the IL-37 serum levels of keloid patients correlated inversely with keloid severity, as determined by the Japan Scar Workshop Scar Scale (JSW) (r = −0.737, P = .0001). In contrast, the serum IL-37 levels did not correlate with patient gender, age, keloid duration, or family history.…”
Section: Il-37mentioning
confidence: 99%
“…39 Many studies have shown that IL-37 plays an important regulatory role in various inflammatory diseases (eg, asthma), autoimmune diseases (eg, rheumatoid arthritis), and tumors. 40 A number of studies show that it is downregulated in patients with severe keloids: the recent cross-sectional study by Khattab et al showed that the IL-37 serum levels of keloid patients correlated inversely with keloid severity, as determined by the Japan Scar Workshop Scar Scale (JSW) (r = −0.737, P = .0001). In contrast, the serum IL-37 levels did not correlate with patient gender, age, keloid duration, or family history.…”
Section: Il-37mentioning
confidence: 99%
“…IL‐37b is the longest transcript variant. IL‐37 expression is detected in numerous tissues and immune cells such as thymus, bone marrow, lymph nodes, NK cells, monocytes, B cells . In recent years, IL‐37 has been shown to have significant effects on inhibiting inflammation in autoimmune diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Although no specific receptor for IL-37 has been identified, a number of studies showed that extracellular IL-37 binds to the alpha chain of the IL-18Rα (36,37), but with much lower binding affinity than that of IL-18 (38). Moreover, IL-37 binds to an IL-18 binding protein (IL-18BP) (39), and to the decoy receptor 8 (IL-R8) (40) via which IL-37 inhibits innate inflammation (35,41,42) in vitro and in vivo (42).…”
mentioning
confidence: 99%